Endoscopic treatment for calcific tendinitis of the gluteus medius: A case report and review - Jian, Chen; Dan, Wang; Gangliang, Wang (Frontiers in Surgery, 2022)
Tendon calcification is a common disease, with the shoulder rotator cuff being the most common site. However, calcific tendinitis of the gluteus medius has rarely been reported. A 64-year-old woman diagnosed with calcific tendinitis of the gluteus medius and experiencing right lateral hip pain with no apparent trigger was reported in this study. After unsuccessful conservative treatment, hip endoscopy was performed on this patient, allowing for a clear view of the “toothpaste-like” lesion in the gluteus medius tendon. A shaver was used to remove the lesion. After eight weeks and 14 months of follow-up, the patient could return to regular daily and social activities. Endoscopic surgery can lead to effective, rapid recovery and minimally invasive clinical outcomes in patients with tendon calcification near the hip joint.